Applications of machine learning and deep learning for privacy and cybersecurity - Lobo, Victor, 1965-; Correia, Anacleto, 1961- (Advances in information security, privacy, and ethics (AISPE) book series., 2022)
"This comprehensive and timely book provides an overview of the field of Machine and Deep Learning in the areas of cybersecurity and privacy, followed by an in-depth view of emerging research exploring the theoretical aspects of machine and deep learning, as well as real-world implementations"--